Lattice Encoding of Cyclic Codes from Skew-polynomial Rings - Ducoat, Jérôme (2015)
We propose a construction of lattices from cyclic codes from skew-polynomial rings. This construction may be seen as a variation of Construction A of lattices from linear codes, obtained from quotients of orders in cyclic division algebras. An application is coset encoding of wiretap space-time codes.